TRANSFORMASI PERAN GURU BAHASA ARAB MELALUI PERSPEKTIF BAHASA SOSIAL: KAJIAN PSIKOLINGUISTIK DI MTSN 2 MEDAN - Ariza Amalia; Aulia Unnisa; Yazim Hidayah; Sahkholid Nasution (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the transformation of the role of Arabic language teachers through the perspective of social language at MTsN 2 Medan. The main focus of this research is to explore the changes in the role of Arabic language teachers, which previously centered solely on teaching the language as a means of religious communication, into a more comprehensive role of connecting students with the language, culture, and values of Islam in a broader context. Using a qualitative approach and case study method, data were collected through in-depth interviews with Arabic language teachers, students, and management staff, as well as direct classroom observations. The results of the study show that Arabic language teachers at MTsN 2 Medan have adopted a more interactive and technology-based approach in their teaching. Teachers also play the role of facilitators, not only teaching language but also shaping students' character and social understanding through contextual and relevant learning. Additionally, the study identifies challenges faced by teachers, such as limited facilities and low student motivation towards learning Arabic. However, the transformation of the teacher's role has a positive impact on the quality of learning, enhancing students' language skills, and strengthening their understanding of Islamic values. This study is expected to provide new insights into the development of Arabic language teaching methods that are more relevant to the social and cultural developments of students in the modern era.